2013
DOI: 10.1371/journal.pone.0063942
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-Like Effects of Antisauvagine-30 in Mice Are Not Mediated by CRF2 Receptors

Abstract: The role of brain corticotropin-releasing factor type 2 (CRF2) receptors in behavioral stress responses remains controversial. Conflicting findings suggest pro-stress, anti-stress or no effects of impeding CRF2 signaling. Previous studies have used antisauvagine-30 as a selective CRF2 antagonist. The present study tested the hypotheses that 1) potential anxiolytic-like actions of intracerebroventricular (i.c.v.) administration of antisauvagine-30 also are present in mice lacking CRF2 receptors and 2) potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Although biphasic effects are possible with CRF 2 receptor antagonist, the dose of Astressin 2 B was carefully selected to avoid such effects. Astressin 2 B has a comparable potency to block CRF 2 receptors as the predecessor antisauvagine-30, but with 10-fold less affinity for CRF 1 receptors (Zorrilla et al, 2013). In addition to this advantage, the concentration of Astressin 2 B used in the present study was approximately fourfold less than the concentration reported to perturb CRF 1 receptor-mediated acoustic startle responses using antisauvagine-30 (Risbrough et al, 2004), and approximately sixfold less for gastrointestinal responses (Chen et al, 2005).…”
Section: Drugs and Chemicalsmentioning
confidence: 70%
“…Although biphasic effects are possible with CRF 2 receptor antagonist, the dose of Astressin 2 B was carefully selected to avoid such effects. Astressin 2 B has a comparable potency to block CRF 2 receptors as the predecessor antisauvagine-30, but with 10-fold less affinity for CRF 1 receptors (Zorrilla et al, 2013). In addition to this advantage, the concentration of Astressin 2 B used in the present study was approximately fourfold less than the concentration reported to perturb CRF 1 receptor-mediated acoustic startle responses using antisauvagine-30 (Risbrough et al, 2004), and approximately sixfold less for gastrointestinal responses (Chen et al, 2005).…”
Section: Drugs and Chemicalsmentioning
confidence: 70%
“…For instance, prior studies using putative CRF 1 or CRF 2 receptor-preferring antagonists provide opposite findings on the role for each CRF receptor type in the stress-induced reinstatement of drug-seeking behavior in cocaine-withdrawn rats (Blacktop et al, 2011;Wang et al, 2007). However, it is possible that the currently available CRF receptor antagonists, especially the putative CRF 2 receptor-preferring antagonists, are poorly selective and might thus interact with both CRF receptor types, at least at the behaviorally active doses usually employed (Zorrilla et al, 2013). In contrast, opiate-withdrawn CRF 2 receptordeficient mice display unaltered CRF 1 receptor-dependent neuroendocrine and behavioral responses (Ingallinesi et al, 2012;Papaleo et al, 2008), suggesting that resilience to the stress-induced reemergence of motivational alterations is specifically because of the lack of functional CRF 2 receptors.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…For this purpose, female and male wild-type and CRF 2 receptordeficient (CRF 2 − / − ) mice are used (Bale et al, 2000). Indeed, although putative CRF 2 receptor-preferring antagonists show higher CRF 2 (versus CRF 1 ) in vitro receptor binding affinity (Grace et al, 2007;Ruhmann et al, 1998), such compounds may interact with both CRF receptors, at least at the behaviorally active doses usually employed (Zorrilla et al, 2013), making it difficult to discern CRF 2 from CRF 1 receptor function. In contrast, CRF 2 − / − mice show preserved CRF 1 receptor function during opiate withdrawal and might thus be used to understand the specific role for the CRF 2 receptor in drug dependence (Ingallinesi et al, 2012;Papaleo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The second is that anatomical studies indicate that CRF1 receptors are the predominant postsynaptic CRF receptors in VTA and that CRF2 receptor expression is not detected by traditional in situ hybridization methods (Van Pett et al, 2000). Another issue to consider in studies using putative selective CRF2 antagonists is that their CRF2/CRF1 ratio selectivity is moderate, and some commonly used CRF2 antagonists like antisauvagine-30 have behavioral effects in CRF2 knockout mice, indicating actions on other receptors (Zorrilla et al, 2013b).…”
Section: Ventral Tegmental Area Media Prefrontal Cortex Orbital Fromentioning
confidence: 99%